2019
DOI: 10.1177/0192512118799756
|View full text |Cite
|
Sign up to set email alerts
|

Mismatch between lower performance and higher trust in the civil service: Can culture provide an explanation?

Abstract: The existing literature on institutional trust leads us to expect that institutional trust is determined by institutional performance. In the context of three South Asian countries (Bangladesh, Nepal and Sri Lanka), we find the opposite – that despite poor performance of the civil service, there is high institutional trust. In this study we examine whether such mismatch can be explained by an authoritarian cultural orientation, which generates unquestioning obedience and loyalty and may contribute to inflated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 38 publications
0
21
0
1
Order By: Relevance
“…The role of culture in an individual's institutional trust has received less attention. Although some studies have explored the source of institutional trust by considering a limited set of values (Yang and Tang, 2010;Dong and Kübler, 2018;Zhai, 2018), some cultural dimensions (Hadarics, 2016;Mahmud, 2017;Pitlik and Rode, 2017;Baniamin et al, 2020), ethnic minorities (Lühiste, 2006;Zmerli 2012;van der Meer and Hakhverdian, 2017) and having a communist background (Mishler and Rose, 2001;Hakhverdian and Mayne, 2012), we did not find any analysis incorporating some cultural theory with a whole range of dimensions covering various elements of culture.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…The role of culture in an individual's institutional trust has received less attention. Although some studies have explored the source of institutional trust by considering a limited set of values (Yang and Tang, 2010;Dong and Kübler, 2018;Zhai, 2018), some cultural dimensions (Hadarics, 2016;Mahmud, 2017;Pitlik and Rode, 2017;Baniamin et al, 2020), ethnic minorities (Lühiste, 2006;Zmerli 2012;van der Meer and Hakhverdian, 2017) and having a communist background (Mishler and Rose, 2001;Hakhverdian and Mayne, 2012), we did not find any analysis incorporating some cultural theory with a whole range of dimensions covering various elements of culture.…”
Section: Introductionmentioning
confidence: 77%
“…However, it is expected that the results are different for authoritarian regimes. Yang and Tang (2010) showed that traditional hierarchical values, Dong and Kübler (2018) and Baniamin et al (2020) showed that authoritarian values, and Zhai (2018) showed that traditional values (e.g., blind loyalty and paternalism) were positively related to institutional trust in China. Grimmelikhuijsen and Meijer (2014) demonstrated that the effect of transparency on institutional trust is less positive in South Korea than in the Netherlands due to the larger power distance in the former country compared to the latter.…”
Section: Cultural Contextmentioning
confidence: 99%
“…People are constrained to choose of their own free will, and leaders’ wishes and directions are the key for most actions. This cultural attribute may be useful in order to understand institutional trust in Bangladesh and Nepal because of their hierarchical culture (Baniamin, 2019; Baniamin et al, 2019). The hierarchical nature of social arrangements in these two countries formed the basis of political structures and governance through patron–client ties (Jamil et al, 2013; Kochanek, 2000; Neher, 1994), political exclusion (Lawoti, 2005), and centralized authority (Riaz & Basu, 2010).…”
Section: Understanding Authoritarian Cultural Orientationmentioning
confidence: 99%
“…Bengali people as an ethnicity make up 95% of its population (Bangladesh National Portal [BNP], 2018), making its society largely homogenous. A recent study also finds the trusting nature of Bangladeshi people, especially their trust in civil institutions and hierarchical social structures (Baniamin et al., 2020). These are all welcoming features of a trusting environment.…”
Section: Trust Group Responsibility For Individual Loans and Aggressive Surveillancementioning
confidence: 98%